2018
DOI: 10.1016/j.jstrokecerebrovasdis.2018.01.030
|View full text |Cite|
|
Sign up to set email alerts
|

Estradiol Protects White Matter of Male C57BL6J Mice against Experimental Chronic Cerebral Hypoperfusion

Abstract: This study demonstrates a potentially protective role for oral estradiol therapy in the setting of white matter injury and declarative memory deficits secondary to murine chronic cerebral hypoperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 74 publications
(79 reference statements)
4
20
0
Order By: Relevance
“…Given that impairments in NOP test outcomes are observed after 1 mo of CCH in the mouse model of VCID we used (Patel et al, 2017;Dominguez et al, 2018;Miyanohara et al, 2018;Ben-Ari et al, 2019), it is not surprising that, in our study, 3 mo of CCH resulted in significant decreases in discrimination indices and novelty preferences based on exploration time. Important are our findings that both RHC-treated mice and the adult F1 offspring of RHC-treated males and females were resilient to such CCH-induced deficits, with both cohorts exhibiting no loss of recognition memory.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Given that impairments in NOP test outcomes are observed after 1 mo of CCH in the mouse model of VCID we used (Patel et al, 2017;Dominguez et al, 2018;Miyanohara et al, 2018;Ben-Ari et al, 2019), it is not surprising that, in our study, 3 mo of CCH resulted in significant decreases in discrimination indices and novelty preferences based on exploration time. Important are our findings that both RHC-treated mice and the adult F1 offspring of RHC-treated males and females were resilient to such CCH-induced deficits, with both cohorts exhibiting no loss of recognition memory.…”
Section: Discussionmentioning
confidence: 75%
“…Novel object preference (NOP) testing is a well-established neurobehavioral tool to assess recognition memory (Antunes & Biala 2012; Vogel-Ciernia et al, 2014; Lueptow et al, 2017; Morena-Castilla et al, 2018). In the VCID model we used, impairments in recognition memory have been confirmed by NOP following 1 month (Patel et al, 2017; Dominguez et al, 2018) of CCH. We commenced NOP testing 3 mo after CCH or sham surgery in both F0 and F1 mice.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that our cohort consisted of exclusively male mice is a potential limitation of this study. Previous studies have suggested that estrogen may have a protective effect against white matter injury [ 61 , 73 ]. This effect, particularly in the setting of inflammatory damage, may be explained by microglial expression of estrogen receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it reproduces metabolic damage in parameters such as: cerebral acidosis, decreased cerebral blood flow, and decreased glucose uptake [52] and has the ability to show the neuroprotective effect of different therapeutic approaches like hypothermia [67,68]. Bilateral ligation of the carotid artery is also used to accentuate white matter damage [69,70] .…”
Section: Experimental Modelsmentioning
confidence: 99%